Evidence of abnormal trading on COVID-19 Pfizer vaccine development information - Andrew N. Mason; Ahmed Elkassabgi (Journal of Risk and Financial Management, 2022)
The 2019 COVID-19 pandemic led to an economic slowdown worldwide and shook the investment world. Pharmaceutical investments were influenced by the anticipation of COVID-19 vaccine developments. Our study examines the real-time impact of public announcements concerning COVID-19 vaccine developments on stock returns and volatilities for Pfizer, Moderna, and the S&P 500. Market Return and Information Event methodology were used to analyze stock activities immediately before important public COVID-19 vaccine development announcements related to Pfizer and Moderna vaccines. This methodology was employed for vaccine news announcements between 2 January 2020 and 4 March 2022. Stock returns and volatility were analyzed with time-series regression analysis. Findings demonstrated that increased trade volatilities occurred immediately prior to COVID-19 vaccine development news was made public. Specifically, Pfizer stock returns were significantly higher (above the mean) immediately before positive COVID-19 vaccine development information was made public. Also, increased volume volatility was observed for Pfizer, Moderna, and the S&P 500 index stocks immediately before positive vaccine development information concerning Pfizer and Moderna vaccines were made public. These findings suggest that the vaccine information may have been leaked before being made public. If so, the findings may indicate that investors were taking advantage of insider information while trying to mitigate the appearance that they engaged in insider trading.
Keywords: 650; COVID vaccine; high-frequency data; Moderna; Pfizer; stock market volatilities